2014
DOI: 10.1109/tap.2013.2287287
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Band Dual-Polarized Compact Bowtie Antenna Array for Anti-Interference MIMO WLAN

Abstract: Smart antennas have received increasing interest for mitigating interference in the multiple-input-multiple-output (MIMO) wireless local area network (WLAN). In this paper, a dual-band dual-polarized compact bowtie dipole antenna array is proposed to support anti-interference MIMO WLAN applications. In the antenna array, there are 12 antennas, six for horizontal polarization and six for vertical polarization. In order to achieve dual linear polarizations and beam switching, six horizontal antennas are placed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…16, all the ECCs of the proposed antenna are under 1.7e-3 in the bands of interest, indicating a good MIMO performance. Note that the larger the distance is between two ports, the lower ECC the results indicate [7]. Therefore, Fig.…”
Section: Results For the Hexagonal Prism Shaped Antennamentioning
confidence: 86%
See 1 more Smart Citation
“…16, all the ECCs of the proposed antenna are under 1.7e-3 in the bands of interest, indicating a good MIMO performance. Note that the larger the distance is between two ports, the lower ECC the results indicate [7]. Therefore, Fig.…”
Section: Results For the Hexagonal Prism Shaped Antennamentioning
confidence: 86%
“…An 18-port MIMO has been proposed in [6] which consists of six tri-polarization antenna elements with three ports mounted on six faces of a cube. A dual-band dual-polarized compact bowtie dipole antenna array for MIMO WLAN is proposed in [7], which consists of 12 antenna elements. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the antenna is compact in size, simple in structure and easy to fabricate. The proposed antenna is smaller in size than the antenna reported in [11][12][13].…”
Section: Introductionmentioning
confidence: 83%
“…In [11], a dual-band MIMO antenna with high port isolation by using an array of printed capacitively loaded loops (CLLs) on the antenna is proposed. A dual-band polarized bowtie antenna array for MIMO WLAN is presented in [12], and a dual-band MIMO antenna with high isolation is proposed by introducing two transmission lines on the top surface of the substrate and etching two slots on the ground [13]. Though good decoupling effect is achieved, such technologies in [11][12][13] require a significant amount of space.…”
Section: Introductionmentioning
confidence: 99%
“…It can be clearly observed that a third resonant frequency f3 appears on the higher end of the two original ones in Antenna C, which does not have the T-shape component, and only f 3 is dominated by the location of the T-shape component in such a way that f 3 gets lower when l T d gets larger, which means a longer extra path for the current flowing would shift the resonant frequency f 3 lower. To achieve the maximum operating bandwidth with the optimized performance for the 3.5 GHz band, l T d = 7.13 mm is chosen, with the simulated impedance bandwidth as 27.8% from 3.13 GHz to 4.14 GHz (VSWR < 1.5), which is significant improvement over those reported slot antenna [17] and Bowtie antenna [18] used in MIMO array. …”
Section: Antenna Elementmentioning
confidence: 99%